Halogen- and hydrogen-bonding triazole-functionalised porphyrin-based receptors for anion recognition. - Gilday, L; White, N; Beer, P (2013)
Iodotriazole and triazole anion recognition groups have been integrated into a picket-fence zinc(ii)-metalloporphyrin scaffold to produce receptors for anion recognition and sensing applications. (1)H NMR and UV/visible spectroscopic investigations reveal both host systems exhibit strong anion binding affinities in a range of solvent media. Importantly, the halogen-bonding iodotriazole-containing porphyrin-based host displays halide binding affinities substantially larger than the protic-functionalised analogue concomitant with a reduced strength of oxoanion complexation.